Transatlantic radicalism : socialist and anarchist exchanges in the 19th and 20th centuries - Jacob, Frank; Kessler, Mario, 1955- (Studies in labour history, 2021)
Radical individuals, like anarchists and socialists in the late 19th and early 20th centuries were quite active when it came to crossing borders, creating radical networks, especially across the Atlantic Ocean. The creation, the functioning, and the impact of these networks will be analysed in detail in the present book.